Melatonin in neuroskeletal biology. (December 2021) - Patel, Anish; Zhou, Edward W.; O'Brien, Morgan; Wang, Xin; Zhou, Shuanhu
Abstract: Osteoporosis and neurodegenerative diseases are common diseases in the aging population. Studies demonstrate the complex communication among skeletal, muscular, and nervous systems and point to the emerging roles of neuromuscular systems in bone homeostasis. The discovery that the nervous system directly regulates bone remodeling implies that osteoporosis is a neuroskeletal disease. Melatonin, a hormone secreted from the pineal gland, is a melatonin receptor 1A (MT1) and 1B (MT2) agonist and influences the function of diverse systems. Melatonin is a pharmaceutical ingredient in numerous medicines, over-the-counter medicines, nutraceuticals, and dietary supplements, which benefit disease prevention and treatment, including osteoporosis and neurodegenerative diseases. This review aims to summarize the recent advances in preventing senile, postmenopausal, and neurodegenerative osteoporosis with melatonin and provide new insights into how neuromuscular systems influence bone homeostasis. More preclinical and clinical studies in neuroskeletal biology will eventually improve the lives of people fighting osteoporosis.